Pharmacokinetics, Tolerability and Pharmacogenetics of DA-8031 After Multiple Ascending Doses in Healthy Male Subjects - Hwang S; Lee DY; Cho JY; Chung JY; Jang IJ; Yu KS; Lee S (Dove Medical Press, 2021)
Sejung Hwang,1 Dae Young Lee,2 Joo-Youn Cho,1,3 Jae-Yong Chung,4 In-Jin Jang,1 Kyung-Sang Yu,1,3 SeungHwan Lee1 1Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, Seoul, Republic of Korea; 2Drug Metabolism and Pharmacokinetics (DMPK), Drug Evaluation, Dong-A ST Research Institute, Gyonggi-do, Republic of Korea; 3Department of Biomedical Sciences, Seoul National University College of Medicine, Seoul, Republic of Korea; 4Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Bundang Hospital, Seongnam, Republic of KoreaCorrespondence: SeungHwan LeeDepartment of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, 101 Daehak-ro, Jongno-gu, Seoul, 03080, Republic of KoreaTel +82-2-2072-2343Fax +82-2-2072-0720Email leejh413@snu.ac.krPurpose: DA-8031 is a novel selective serotonin reuptake inhibitor for the treatment of premature ejaculation. This study investigated the pharmacokinetics, safety and tolerability of multiple oral doses of DA-8031. In addition, a genetic analysis was explored to evaluate the effect of genetic polymorphisms on the pharmacokinetics of DA-8031.Subjects and Methods: A dose block-randomized, double-blind, placebo-controlled study was conducted in 3 dose groups with 20, 30 and 40 mg of DA-8031. Healthy male subjects were randomized to DA-8031 or placebo at a 4:1 ratio in each dose group of 10 subjects by oral administration once daily for 7 consecutive days. Serial blood and urine samples were collected for the pharmacokinetic evaluation, and the pharmacokinetic-related genes were analyzed by DMETTM plus. A safety evaluation was conducted including adverse events (AEs) monitoring and 12-lead electrocardiogram (ECG).Results: The plasma DA-8031 concentration reached the maximum concentration (Cmax) in 2.2 to 3.0 h and was eliminated with a mean half-life of 25.5 to 26.7 h at steady state. The accumulation index of DA-8031 ranged 2.3 to 2.8. The systemic exposure of DA-8031 of the CYP2D6 intermediate metabolizer (IM) was significantly higher compared to the CYP2D6 poor metabolizer (PM). There were no clinically significant QTc interval changes, and all the adverse events were mild.Conclusion: After multiple oral doses of DA-8031 20, 30, and 40 mg in this study, the systemic exposure of DA-8031 increased in a more than dose-proportional manner with the increasing doses, and DA-8031 was generally well tolerated. In addition, the genetic polymorphisms of CYP2D6 have an impact on the pharmacokinetics of DA-8031.Keywords: selective serotonin reuptake inhibitors, clinical pharmacology, phase 1 study, pharmacogenomics